Edmund Wilson : Centennial Reflections - Dabney, Lewis M. (Book collections on Project MUSE., 2014)
Edmund Wilson helped shape American letters from the early 1920's through the mid-'60s. He remains a presence in our literary culture, and his accounts of art and society have influenced a younger generation of readers and thinkers. This vibrant collection emerges from symposiums held at the Mercantile Library and at Princeton University in 1995, Wilson's centennial year. At these occasions, prominent critics, literary journalists, and historians aired a variety of points of view about his work and personality. Assembled and edited by Lewis Dabney, this book shows new intellectual voices in.